PENGARUH KONSELING KELOMPOK MELALUI TEKNIK REINFORCEMENT POSITIVE UNTUK MENINGKATKAN DISIPLIN BELAJAR SISWA DI SMAN 1 KECAMATAN MUNGKA - Widya Arianti; Alfi Rahmi; Dodi Pasila Putra; Syawaluddin Syawaluddin (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
This study aims to determine the effect of group counseling with positive reinforcement techniques on student learning discipline at SMAN 1 Mungka District. The problem identified is the low learning discipline of students, such as being late for class, making noise during lessons, and not taking learning activities seriously. This study used a quantitative experimental method with a One Group Pretest-Posttest design, with a sample of 43 students of class XI IPA and XI IPS selected through purposive sampling. Data were collected using a questionnaire and analyzed using the Wilcoxon test. The results showed that students' learning discipline before being given group counseling services was in the moderate category, with an average score of 66.40. After the treatment, students' learning discipline increased to a high category with an average score of 95.50. The Wilcoxon test results show a p-value of 0.005, which is smaller than 0.05, which means that the alternative hypothesis is accepted. Thus, group counseling using positive reinforcement techniques is proven effective in improving students' learning discipline.